(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2022)
The relationship between the dynamics of creatine kinase activity in the blood serum and the volumetric blood flow velocity in the cerebral hemispheres in different periods of chicken development was assessed. A uniform increase in blood flow in the brain was accompanied by a uniform increase in the anatomical lumen (D2). internal carotid artery, and maintaining the same level of linear blood flow velocity (V), parietal shear stress (t V/D). development of chick embryos. Such an increase in the activity of CC- (as an energy source) throughout the entire period of embryogenesis can be considered as a physiological mechanism that maintains an increase in the linear velocity of the internal carotid artery (D2) and blood, and the V/D index of the wall of the main arteries at the same level.